Ironing it out : seven simple steps to resolving conflict - Lickson, Charles P. (Crisp Pub. Menlo ParkUS, 1996)
Analyses conflict. Provides seven steps for ironing out conflict beginning with, removing all masks and ending with acknowledging and preserving the value of the relationship. Discusses the application of the seven steps to resolving conflicts in the family, workplace, public etc. Views conflict as a potentially creative process.